2017
DOI: 10.1590/1983-40632016v4745189
|View full text |Cite
|
Sign up to set email alerts
|

Seed quality of common bean accessions under organic and conventional farming systems1

Abstract: Agrobiodiversity is essential for a sustainable food production, and the knowledge of the potential characteristics of landrace seeds may prompt farmers to adopt the habit of seed conservation for this species. This study aimed at categorizing landrace and commercial common bean (Phaseolus vulgaris L.) accessions, according to the physiological quality (viability and vigor) of seeds produced in the field, during two growing seasons, under organic and conventional farming systems. Germination percentage, field … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 13 publications
1
4
0
1
Order By: Relevance
“…The cultivars were previously characterized in studies with nine consecutive crop seasons using selffertilization, which favored the homogeneity and stability of the populations. The cultivars used were determined by their morpho-agronomic characteristics and seed physiological qualities (MICHELS et al, 2014;EHRHARDT-BROCARDO;COELHO, 2016;GINDRI et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cultivars were previously characterized in studies with nine consecutive crop seasons using selffertilization, which favored the homogeneity and stability of the populations. The cultivars used were determined by their morpho-agronomic characteristics and seed physiological qualities (MICHELS et al, 2014;EHRHARDT-BROCARDO;COELHO, 2016;GINDRI et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Common bean (Phaseolus vulgaris L.) crops are important in the whole world as source of carbohydrates, proteins, and minerals. Studies on vigor of common bean plants have sought to identify correlations between yield (MONDO; NASCENTE; CARDOSO NETO, 2016), production systems (GINDRI et al, 2017), genetic diversity (GINDRI; COELHO, 2019), biochemistry composition (CASSOL et al, 2016) and enzymatic activity (MORIYA et al, 2015). However, such studies do not consider the dynamics of seed reserve mobilization (SRM) in control of internal seed quality and selection of high-vigor common bean genotypes, which is an important strategy to be explored for this purpose.…”
Section: Introductionmentioning
confidence: 99%
“…The sum of ranks index was associated with the Scott-Knott clustering method to characterize the accessions, in terms of physiological seed quality. GINDRI et al (2017) have already demonstrated the genetic diversity in the physiological quality of the seeds, shortly after harvest (before sample storage), in terms of viability and vigor, in the bean landraces accessions. However, seed deterioration begins after the seed reaches physiological maturity and continues to lose its ability to germinate, so that the evaluation of the physiological potential of the seeds soon after harvesting is necessary for the evaluation of their behavior during storage.…”
Section: Data Mining and Selection Index Of Mulamba And Mock (1978)mentioning
confidence: 97%
“…La calidad fisiológica está condicionada por la constitución genética de los genotipos. Algunos trabajos en frijol bajo fertilización orgánica, no existió diferencias en la calidad fisiológica de las semillas (germinación, longitud de plántula y emergencia), entre lo orgánico y lo convencional (Medeiros et al, 2017). La calidad fisiológica, y el vigor de la semilla, están influenciados por cambios en la composición química, proteína, principalmente soluble, almidón y contenido de azúcar (Henning et al, 2010).…”
Section: Fuentes De Variaciónunclassified